2013
DOI: 10.1007/s00431-013-2207-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunization status in children with inflammatory bowel disease

Abstract: Inflammatory bowel diseases have an increased risk of infections due to immunosuppressive therapies. To report the immunization status according to previous recommendations and the reasons explaining a delay, a questionnaire was filled in by the pediatric gastroenterologist, concerning outpatients, in six tertiary centers and five local hospitals, in a study, from May to November 2011. One hundred and sixty-five questionnaires were collected, of which 106 Crohn's diseases, 41 ulcerative colitis, and 17 indeter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…For example, the uptake of influenza vaccine was 37.5% in South Korea [14], 19-28% in Germany [15,16] and 28% in the United States [1]. The uptake amongst pediatric IBD patients in France was 21.8% [5].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, the uptake of influenza vaccine was 37.5% in South Korea [14], 19-28% in Germany [15,16] and 28% in the United States [1]. The uptake amongst pediatric IBD patients in France was 21.8% [5].…”
Section: Discussionmentioning
confidence: 97%
“…The most common is lack of awareness (58%), however, fear of side effects (33%) and fear of disease activation (5%) are also factors which need to be addressed [5]. Evidence suggesting that influenza vaccine causes IBD activation is limited to case reports, and in fact there is robust data indicating the opposite -IBD patients do not require additional health services following vaccination [17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Concerns were analysed in more depth for specific vaccines. Articles looking at different vaccines without providing data on each vaccine separately [9][10][11][12][13][14][15][16] and vaccines for which there were only a handful of articles available [17][18][19][20][21][22][23][24][25][26] were excluded from the in depth analysis.…”
Section: Resultsmentioning
confidence: 99%
“…13 -17 A study of 165 pediatric patients with IBD revealed vaccination rates of 22% for influenza, 32% for pneumococcus, 38% for hepatitis B, and 87% for diphtheria-tetanusacellular pertussis. 14 …”
Section: Vaccination Statusmentioning
confidence: 99%